2023
DOI: 10.1037/sah0000307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of affirming values on self-compassion and mental health treatment stigma.

Abstract: Stigma surrounding mental disorders deters many people from treatment, and prior studies have shown that internalization of stigma is inversely correlated with self-compassion. We examined the effect of a valuesaffirmation task shown to increase state self-compassion on attitudes about mental disorders and their treatment. Participants completed measures of their mental health attitudes and experiences prior to a valuesaffirming writing task or control writing task, and afterward completed measures of state se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…We averaged the items (with the nine negative items reversed) to create a scale with α = 0.929 at pretest and 0.934 at posttest. Glazer et al (2021) found that this scale correlated significantly with Trait Self-Compassion subscales reflecting high Self-Kindness and low Self-Judgment, even after controlling for state mood and socially desirable responding.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…We averaged the items (with the nine negative items reversed) to create a scale with α = 0.929 at pretest and 0.934 at posttest. Glazer et al (2021) found that this scale correlated significantly with Trait Self-Compassion subscales reflecting high Self-Kindness and low Self-Judgment, even after controlling for state mood and socially desirable responding.…”
Section: Methodsmentioning
confidence: 86%
“…State Self-Compassion. We measured state self-compassion through ratings of 18 adjectives (e.g., accepted, at peace, inadequate) intermixed with the PANAS items (as in Glazer et al, 2021). Participants rated each from very slightly or not at all (1) to extremely (5).…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that self-compassion improves mental health by buffering against the effects of societal SV stigma. For example, research shows that greater dispositional self-compassion weakens the relationship between stigmatizing experiences and stigma internalization (Chong et al, 2023; Glazer et al, 2023; Heath et al, 2018), such that SV survivors who are self-compassionate report lower self-blame and shame (Carvalho & Guiomar, 2022). Self-compassion may have this effect by encouraging survivors to reject stigmatizing messaging around SV, maintain a sense of self-worth in the face of this messaging (Barnard & Curry, 2011; Wong et al, 2019), and encourage adaptive coping strategies such as self-care and seeking social support (Livingston & Boyd, 2010).…”
Section: Internalized Sv Stigma and Perceived Control Over Recoverymentioning
confidence: 99%
“…Since internalized stigma is frequently observed in mental illnesses like BD, several researchers state that the concept of self‐compassion might be important for patients to behave themselves understandingly and kindly (Brohan et al, 2011; Edwards, 2022; Heath et al, 2018; Mateer et al, 2023; Wong et al, 2019). Self‐compassion involves being open to one's own suffering, being able to contact this suffering, and easing it without avoidance and a desire for self‐healing with kindness.…”
Section: Introductionmentioning
confidence: 99%